Why is cancer becoming a global endemic today? - Rasheed, Zafar (International Journal of Health Sciences, 2020)
Despite the availability of modern chemotherapeutic approaches and the power of excellent molecular research and persistent investigative efforts, cancer remains an epidemic and the question – “why is cancer becoming an endemic today?” remains unanswered completely. If we look around, we have hospitals, doctors, nutritionists, health professionals, other than these fitness centers, foods’ supplements, and every possible thing, but if we look at the statistics of the cancer prevalence, which is rising exponentially in all over the globe. Recently, the Centers for Disease Control and Prevention pointed out that the rates of some types of cancers to the year 2020 are reducing or stabilizing, but the overall number of cancer cases and deaths still continues to increase.[1] It is so easy for us to believe on social media, television media, or on the opinion of general people about the factors associated with the onset of cancer such as air pollution, food contamination such as meat, fruits, vegetables, and water stuff are unhygienic. Of course, these are the factors especially air pollution are somewhat associated with cancer.[2] However, there are five major commonalities which are directly associated with the onset of cancer. These commonalities were defined by Luke Coutinho in his excellent FaceTime video on cancer prevalence.[3] Luke Coutinho, he is an award-winning globally renowned Holistic Lifestyle Coach and practicing in the field of Integrative and Lifestyle Medicine (https://www.lukecoutinho.com/). He and his colleagues pulled out the data from hundreds of cancer patients over the past 1 year and have looked for commonality in the lifestyles of the cancer patients before they got cancer.[3] The data were from cancer patients across India, Europe, Mexico, Russia, United States, Australia, Thailand, Vietnam, Taiwan, and Japan. The outcome was very surprising, the data did not show a significant correlation of cancer with obesity, exposure to chemicals, drinking, and smoking. Interestingly, the data showed the direct relation of cancer onset with the five commonalities such as chronic constipation, chronic acidity, sleep deprivation, chronic emotional stress, and sedentary lifestyle.[3] Let us support the data pulled by Luke Coutinho and discuss their correlation with cancer in terms of scientific and general views. Chronic constipation, several reports have shown that the people who have cancer or who develop cancer at some point in their life or at the current point in their life, they have chronic constipation.[4,5] We have to understand that chronic constipation is a major health problem, during its progression, we actually storing toxic waste in our system. These toxic wastes are very harmful for our organs, especially to the liver and kidneys. The unusual storage of toxins in the body is known to produce cancer stimulatory substances,[6,7] which later on initiate or promote mutations that have a direct association with the rapid growth tumor cells.[4-7] Chronic acidity is another commonality that was also reported to play a role in cancer onset and progression.[8,9] It makes sense when our body is acidic, it means that it gives an acidic environment for cancer cells to mutate, spread, and grow faster.[8,9] Third commonality among cancer patients is sleep deprivation, which also has a direct association with the cancer onset. The simple science behind sleeping is the regulation of hormone melatonin.[10] During sleeping, we produce melatonin, which is now well proven as an anti-cancer hormone.[11] Enough sleep produces the right amount of melatonin, which makes our immunity stronger and prevents us from the proliferation of cancer cells.[10,11] Chronic emotional stress is another commonality that was found in most of the cancer patients.[3,12] Luke Coutinho and colleagues analyzed responses of a question that was asked to almost all cancer patients – what was going on in their life for the past 6 months to a year maybe even 2 years before the onset of cancer, as cancer just does not grow overnight. It is accumulating in the body from 6 months to a year or maybe more and they found that extreme emotional stress in most of the studied cancer patients. It does not mean that if we are in stress today, then will have cancer tomorrow. Each one of these cancer patients could point out actually about prolonged chronic emotional stress. For example, some of them were divorced, some were separated from their lovers, some of them lost their children, parents, and some were having property or financial issues, etc. These data have also been well supported by other studies, Chiriac et al. recently published a systematic review on the stress and the incidence of cancer and the data revealed a significant association between stress and cancer.[12] Therefore, it is now confirmed that emotional stress is key to cancer onset. Besides these, sedentary lifestyle is also commonality reported in most of the cancer patients and also found to be well connected with any of the above mentioned commonalities.[3,13] Let us ponder what will happen, if we will have an uninterrupted sedentary lifestyle, we may gain weight, or get acidic or constipated, which land up some sort of emotional stress. These data are also very well supported by various other studies.[13] A study performed by Kerr et al. showed that the lifestyle factors associated with cancer. They reported that physical activity, sedentary behaviors, and diet all are linked to cancer.[13] Let us discuss how we can overcome these commonalities so that we protect ourselves from cancer. The most important thing is the surplus intake of water. Several reports showed that at least 90% of the people have never fallen sick if they had taken care of their water intake.[14,15] Low intake of water reduces the power of immunity and also causes constipation and increased acidity.[14-16] Other than these, less water intake also reduces our control of the brain, which means loss of cognitive thoughts, emotions, and intends to become powerless to handle the day-to-day stress. All mentioned commonalities were reported to be associated with less intake of water and subsequently connected with the onset of cancer.[17,18] Therefore taking water in an appropriate amount not only prevents us from cancer-associated commonalities but also protects us from cancer. Besides water intake, our thoughts also play a major role, if we think that we are sick then we will be sick, let’s talk about the relation of cancer with genetics in this context. We all know that genetics plays a role in the onset of cancer,[19] but it does not mean that if our parents have cancer, we also will have cancer. Luke Coutinho in his conversation described in an excellent way by giving the reference of a book called “The biology of belief written by Bruce Lipton.[20]” This book tells us that we have good genes as well as bad genes, if we create the wrong environment in our body and around, then our bad genes will express themselves. So even if we have inherited cancer genes from our parents, we need to create a good conducive environment inside and outside, this escape us from the expression of cancer-associated genes.[20] Therefore, our thoughts or the environment that we have created have a direct impact on every single gene and that definitely plays a role not only to prevent us from the onset of cancer but also protect from cancer progression. In short, there are several ways described above to prevent us from the cancer onset or to recover from cancer without spending any penny. We need to think about the association of cancer with chronic constipation, chronic acidity, sleep deprivation, chronic emotional stress, or sedentary lifestyle and endeavor to resolve them as early as possible.